Modification of The Gasik Game version 2.0 to improve 21st Century Skills for Junior High School - Haya, Frilisa Dliyaul; Hartono, Hartono; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2020)
The 21st-century skill standards in Indonesia include 4Cs (critical thinking, creativity, communication, and collaboration); ICTs (Information, Media and Technology Skills); Character Building; and Spiritual Value. All 21st-century skills need to be possessed by students as a provision to face all the challenges of life. Therefore, we need a guide who can instill all skills. The purpose of this study was to improve the students' 21st-century skills.Ã‚Â The 21st-century skills in this study focused on increasing 4Cs skills. The development model used is Analyze, Design, Develop, Implement, and Evaluate (ADDIE Model). Research subjects were 75 eighth-grade students of junior high school. Data collection method used was an experimental method. Data collection used a product assessment questionnaire, an observation rubric of 21st-century skills, and tests. Meanwhile, the product content validity test uses the v Aiken index. The modified Gasik game (Gasik version 2.0) received ratings from the experts on the material aspect of 83.68% and in the media aspect of 87.61%.Ã‚Â The value of the content validity v Aiken is 0.82 with a high category so that the Gasik 2.0 game can be stated as very good to be applied to 21st-century learning. The n-gain value between the pretest and posttest values in the experimental class is 0.12, while in the control class is -0.01. The results of the analysis indicate that the use of the Gasik 2.0 game can grow 4Cs skills with low categories.